Chaetotaxy of first-stage butterfly larvae, with improved homologies and nomenclature for lepidoptera setae and sensilla - Scott, James A., author; James A. Scott, publisher (Colorado State University. Libraries, 2020)
This paper has two goals. The first goal, of interest to all Lepidopterists, is to improve the names given to the setae and olfactory pores and sensillae: new homologies of the setae are presented including those on the last abdomen segment (good homologies on this segment are presented for the first time); a name is assigned for every seta and sensilla of the entire body including mouthparts, building upon Hinton (1946); different names are assigned to non-homologous setae that formerly were confused by having the same name; figures and an alphabetical glossary of structures are presented for users. The second goal is to present new data on butterflies, including setal maps for every subfamily known (only Pseudopontiinae and Calinaginae now lack setal maps), an improved key that includes additional subfamilies and genera, and diagnostic characters for each family, subfamily, and tribe. Scott (1986a) presented setal maps for selected first stage butterfly larvae and presented a key to all known North American subfamilies. Scott (1985, 1986b) and Scott and Wright (1990) used characters of first stage larvae as well as many other characters to deduce the phylogeny of butterflies.
Keywords: Papilio. New Series; Butterflies; Lepidoptera